Effects of shock pressure and temperature on titanomagnetite from ICDP cores and target rocks of the El’gygytgyn impact structure, Russia - Kontny, Agnes; Grothaus, Lea (Studia Geophysica et Geodaetica)
a1_The aim of this study was to investigate the effect of meteorite impacts on magnetic properties including magnetic susceptibility and the Verwey transition of Ti-poor titanomagnetite of volcanic rocks from the 3.6 Ma old El’gygytgyn impact structure located in the Okhotsk-Chukotka volcanic belt in north-eastern Russia. The target rocks consist mainly of rhyolite with some andesites, and is a rare example of impact structures within volcanic target rocks on Earth. 27 samples from outside the crater, the crater rim and from the depth interval 316 to 517 m below lake bottom (mblb) of the El’gygytgyn ICDP drilling were studied. A significant decrease of the average specific magnetic susceptibility by around 90% was observed between felsic volcanic rocks from the surface (18.1 × 10-6 m3/kg) and the drill cores from near the crater central uplift (1.9 × 10-6 m3/kg). Ferrimagnetic Fe-Ti oxide assemblages (Verwey transition temperature, TV: -161 to -150°C, Curie temperature, TC: 451 to 581°C), occurring in all studied samples, differ significantly. At the surface titanomaghemite is ubiquitously associated with titanomagnetite. The drill cores lack titanomaghemite, but either show a transformation into titanomagnetite and ilmenite or a strong fragmentation associated with a second TV between -172 and -188°C. Reversible curves of temperature dependence of magnetic susceptibility in the suevite indicate high depositional temperatures of at least 500°C. In the polymict and monomict impact breccia mechanical deformation of titanomagnetite and temperatures of at least 200-350°C related to the shock are suggested from temperature dependent magnetic susceptibility cycling. Lowtemperature oxidation along strongly brecciated grain surfaces in titanomagnetite is suggested to cause the lower TV and we suggest that this phenomenon is related to postimpact hydrothermal activity. a2_The strong magnetic susceptibility decrease at El’gygytgyn is mainly influenced by shock, and post-impact hydrothermalism causes a significant ...